Multimodal engagement through a transmedia storytelling project for undergraduate students - Melissa Shamini Perry, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Transmedia storytelling has great potential in the field of education and research on its applications and benefits in teaching and learning is growing. This paper explores the use of transmedia storytelling as a multimodal pedagogical tool for tertiary students. This paper explicates the design and application of a transmedia storytelling project in increasing multimodal engagement for undergraduate students from various faculties. A case study of a transmedia storytelling campaign conceptualised and produced by undergraduate students from a Malaysian public university was analysed for evidence of multimodal engagement. Students’ project output including campaign pitches, campaign designs and artefacts such as scripts, storyboards, posters, photos and videos submitted via digital formats were collated and analysed using a multimodal framework. Post-assessment reflections submitted by students were also analysed. The findings of the case study revealed that the conceptualisation and production of a transmedia storytelling campaign consisting of a short film, book and social media page enabled students to engage with multiple modalities and develop various skills and competencies. Analysis of campaign artefacts and student reflections found that the use of this novel pedagogy enabled students to engage with visual and spatial, linguistic, audio, gestural and technical digital modes of meaning as well as develop literary competencies and creative thinking skills through this project. This paper paves the way for further exploration of the use of transmedia storytelling as a multimodal pedagogical tool to develop various literacies, educational competencies as well as 21st century skills amongst tertiary students.